Crossed aphasia: a PET follow up study of two cases. Issue 6 (June 1993) - Cappa, S F; Perani, D; Bressi, S; Paulesu, E; Franceschi, M; Fazio, F
Abstract : Two cases of aphasia after right hemispheric stroke in right handed patients are described. The first patient had a severe mixed transcortical aphasia, apraxia and neglect after a lesion involving the right lenticular nucleus and periventricular white matter; aphasia was still present after three months. The second patient had a mild, transient fluent aphasia after a small right hemispheric periventricular lesion. Studies with [18F]FDG and positron emission tomography (PET) showed functional depression extending to the structurally unaffected left hemisphere in both patients in the acute stage. After three months, in the patient with persistent aphasia, metabolism was still reduced in the right hemisphere, with some recovery of hypometabolism on the left, while metabolic values had returned to normal in the patient with full language recovery. A close parallelism between glucose metabolism and clinical course in crossed aphasia is shown, as well as the presence of a functional involvement of the structurally unaffected left hemisphere in the acute stage.